Regulating the Rise of China - Peters, Michael. author. aut Link
XV, 309 p. 3 illus., 1 illus. in color.
Keywords: This book revises the existing account of the first Rudd Government's engagement with China, placing Australian foreign direct investment screening policy at the centre of the story. At the time, the Rudd Government was accused of holding an unnecessarily interventionist approach to Chinese Sovereign-Owned Enterprise investments into the Australian mining sector. This book claims that the Australian Government had a deep and coherent understanding of the problem posed by Chinese investments that went well-beyond any simplistic 'China Inc.' or geopolitical threats. The key policymakers believed that the Chinese state-directed investments threatened the integrity of the liberal governance structures on which the Australian state is founded, and so Australian sovereignty itself. While the response of the Rudd Government was largely ineffectual, the logic underpinning it remains the best framework for guiding Australia's engagement with China into the 2020s, as well as the engagementof other liberal states coming to grips with China's rise. Michael Peters studied International Relations at the University of New South Wales, Australia. He teaches International Relations and works on the editorial and publicity teams of the Economic and Labour Relations Review.